(untitled) (European Journal of Engineering Science and Technology, 2019)
The paper presents the optimization of the weight of elements printed in Fused Deposition Modelling (FDM) technology. For this purpose, the static bending test was carried out. The test was carried out in compliance with PN-EN ISO 178:2011 standard. Samples were made of polylactide (PLA). The influence of such parameters as filling density and type of filling or its orientation was examined. The collected data allowed to calculate the maximum stresses in the material used to improve the Silesian Greenpower car. Compared to infill patterns and their density allowed to choose the optimal printing method.